Anti-CD4-mediated selection of Treg in vitro - in vitro suppression does not predict in vivo capacity to prevent graft rejection. - Oliveira, V; Sawitzki, B; Chapman, S; Appelt, C; Gebuhr, I; Wieckiewicz, J; Long, E; Wood, K (2008)
Regulatory T cells (Treg) have been shown to play a role in the prevention of autoimmune diseases and transplant rejection. Based on an established protocol known to generate alloantigen reactive Treg in vivo, we have developed a strategy for the in vitro selection of Treg. Stimulation of unfractionated CD4(+) T cells from naive CBA.Ca (H2(k)) mice with C57BL/10 (H2(b)) splenocytes in the presence of an anti-CD4 antibody, YTS 177, resulted in the selection of Treg able to inhibit proliferation of naive T cells. In vivo, the cells were able to prevent rejection of 80% C57BL/10 skin grafts when co-transferred to CBA.Rag(-/-) mice together with naive CD45RB(high)CD4(+) cells. Purification of CD62L(+)CD25(+)CD4(+) cells from the cultures enriched for cells with regulatory activity; as now 100% survival of C57BL/10 skin grafts was achieved. Furthermore, differentiation of Treg could be also achieved when using purified CD25(-)CD4(+) naive T cells as a starting population. Interestingly, further in vitro expansion resulted in a partial loss of CD4(+) cells expressing both CD62L and CD25 and abrogation of their regulatory activity in vivo. This study shows that alloantigen stimulation in the presence of anti-CD4 in vitro provides a simple and effective strategy to generate alloreactive Treg.